A prospective cohort study on the impact of smoking on soft tissue alterations around single implants. Issue 9 (5th May 2014) - Raes, Stefanie; Rocci, Antonio; Raes, Filiep; Cooper, Lyndon; De Bruyn, Hugo; Cosyn, Jan
Abstract Objectives To compare smokers to non‐smokers in terms of soft tissue alterations following single implant treatment in healed bone. Material and methods Non‐smoking and smoking patients with sufficient bone volume in need of a single implant in the anterior maxilla (15–25) were consecutively recruited in three centres. Conventional single implant surgery was performed and an immediate provisional crown was installed. Eight to 12 weeks later, the latter was replaced by a permanent one (baseline). Papilla regrowth and midfacial recession was registered after 2 years of function. Results The sample consisted of 39 non‐smokers (21 females; mean age 42) and 46 smokers (22 females; mean age 45). Smokers had three early failures, whereas all implants integrated successfully in non‐smokers. Statistically significant papilla regrowth was observed in non‐smokers (distal 0.63 mm, mesial 0.76 mm), whereas smokers showed stable papillae (between cohorts: P ≤ 0.025). Midfacial soft tissue level demonstrated statistically significant regrowth in non‐smokers (0.53 mm), whereas it remained stable in smokers (between cohorts: P = 0.004). Conclusion Smokers failed to demonstrate papilla regeneration and showed more midfacial recession following single implant treatment when compared to non‐smokers.